Ensartinib as a neoadjuvant therapy for stage IIIA non-small cell lung cancer patients with EML4-ALK fusion: a case report and literature review - Zhang, Hao; Xia, Wei; Zhang, Yifan; Bao, Shihao; Zeng, Jingtong; Li, Xianjie; Zhang, Bo; Wang, Hanqing; Xu, Song; Song, Zuoqing (Frontiers in Oncology, 2025)
Anaplastic lymphoma kinase (ALK) inhibitors have shown efficacy in treating ALK-positive advanced non-small cell lung cancer (NSCLC) patients. However, the effectiveness of ensartinib neoadjuvant therapy remains ambiguous. Herein, we reported that preoperative systemic treatment with the ALK inhibitor ensartinib can be beneficial for treating initially inoperable tumors. In this study, we present a case of a 60-year-old female patient who was diagnosed with stage IIIA (cT2aN2aM0, ninth TNM stage) lower left lung adenocarcinoma harboring an EML4-ALK fusion. After three months of therapy, the neoadjuvant treatment with ensartinib provided a partial response, with significant tumor and lymph node shrinkage. Preoperative ensartinib neoadjuvant therapy for NSCLC is safe and effective. Nevertheless, clinical trials can be conducted in the future to validate our results. Moreover, we performed multiple immunofluorescence staining analyses on samples before and after neoadjuvant therapy, observed and compared the changes in the expression of relevant immune cells (CD8+ T cells, macrophages, PD-1, and PD-L1), and performed a simple analysis.